Multifunctional Nucleic Acids for Tumor Cell Treatment - Pofahl, Monika (Mary Ann Liebert, Inc., 2014)
We report on a multifunctional nucleic acid, termed AptamiR, composed of an aptamer domain and an antimiR domain. This composition mediates cell specific delivery of antimiR molecules for silencing of endogenous micro RNA. The introduced multifunctional molecule preserves cell targeting, anti-proliferative and antimiR function in one 37-nucleotide nucleic acid molecule. It inhibits cancer cell growth and induces gene expression that is pathologically damped by an oncomir. These findings will have a strong impact on future developments regarding aptamer- and antimiR-related applications for tumor targeting and treatment.